2022
DOI: 10.1017/gmh.2022.27
|View full text |Cite
|
Sign up to set email alerts
|

The relation of unrest-related distress with probable depression during and after widespread civil unrest

Abstract: Background This study investigated whether subjective unrest-related distress was associated with probable depression during and after the 2019 anti-ELAB movement in Hong Kong. Methods Population-representative data were collected from 7157 Hong Kong Chinese in four cross-sectional surveys (July 2019–July 2020). Logistic regression examined the association between subjective unrest-related distress and probable depression (PHQ-9 ⩾ 10), stratified by the number of conflicts/protests acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…A higher probability of depression amid and after widespread civil unrest in Hong Kong between July 2019 and July 2020 was reported (Tao et al 2022 ). Similarly, another study in Hong Kong reported a high prevalence of anxiety and stress brought on by the June 2019 protests and COVID-19 (Hou et al 2021 ).…”
Section: Findings and Discussionmentioning
confidence: 96%
“…A higher probability of depression amid and after widespread civil unrest in Hong Kong between July 2019 and July 2020 was reported (Tao et al 2022 ). Similarly, another study in Hong Kong reported a high prevalence of anxiety and stress brought on by the June 2019 protests and COVID-19 (Hou et al 2021 ).…”
Section: Findings and Discussionmentioning
confidence: 96%